The hand at work : the poetics of poiesis in the Russian avant-garde - Strätling, Susanne (Academic Studies Press, 2021)
"Art = New Vision. This formula shaped the avant-garde. With moving images abruptly expanding the boundaries of the visible world, new printing techniques triggering a pictorial turn in graphic art, and literature becoming almost inseparable from visual media we still regard the avant-garde as heyday for modernisms obsession with the eye. But what are the blind spots of this optocentrism? Focusing on the gestures of giving, touching, showing and handcrafting, this study examines key scenes of tactile interaction between subject and artifact. Hand movements, manual maneuvers and manipulations challenge optics and expose the crises of a visually dominated perspective on the arts. The readings of this book call for a revision of an optically obscured aesthetics and poetics to include haptic experience as an often overlooked but pivotal part of the making as well as the perception of literature and the arts"--